Effect of curing conditions on the strength of soil cement - Salisa Chaiyaput; Nakib Arwaedo; Namthip Kingnoi; Trong Nghia-Nguyen; Jiratchaya Ayawanna (My University, 2022)
An experimental program was directed to the evaluation of the strength of soil (ball clay)-cement, and soil (soft clay)-cement samples with different curing conditions; tap water, lime-saturated water, plastic wrapping, and open ambient air at 28 days. The compression, and the scanning electron microscopy results were used to describe the effect of curing conditions on the compressive strength of soil-cement samples. The compressive strength of soil-cement samples was ~ 50% that of the plain cement sample. The compressive strength of the soft clay-cement samples was slightly higher than the ball clay-cement samples because of the coarse particles of soft clay containing a high amount of quartz, allowing the water to react with cement powder and increased the strength of soil-cement samples. The tendency of compressive strength development in the soil-cement samples was similar to that of the cement sample. The highest compressive strength was obtained for the lime-saturated water cured samples, suggesting a higher rate of hydration process by the protection of CaCO3 leaching from cement in the lime water. Thus, the compressive strength in soil-cement samples was enhanced by the binding of cement hydration products between the adjacent soil particles.
Keywords: Grouting, Rheology, and Soil Mechanics